The prizewinners of Piedmont Place - Doyle, Bill H., 1968- (Random House, 2016)
"Eleven-year-old Cal must convince his lovably wacky family to compete in a contest where the winners are granted twenty minutes to grab anything from King Wonder's world-famous shop"--